An introduction to γ3 a new versatile ultralow background gamma spectrometer. Background description and analysis. (April 2015) - Cagniant, A.; Douysset, G.; Fontaine, J.-P.; Gross, P.; Petit, G. Le
Abstract: The γ 3 setup has been designed as a versatile, high sensitivity spectrometry platform. State-of-the art techniques have been implemented to reduce its background to minimum level even though the system is installed at ground level. The shield design and background performance of the setup are presented. The spectrometer is composed of three identical HPGe detectors for high detection efficiency or coincidence measurement and can accommodate several sample geometries. Its shield includes three layers of increasing purity lead, a cosmic veto, an inner borated polyethylene layer, and a radon-free gas injection system. The spectrometer normalized background count rate is 4.4 counts per minute kgGe −1 (in the 40–2500 keV energy range). Its background characteristics, cosmic veto efficiency, and radon-free gas injection performances are discussed. Highlights: A new ultra-low background gamma spectrometer was installed at surface level. Its shielding design and cosmic veto configuration are presented. Its background characteristics are detailed and compared with existing systems. Radon-free gas injection effects in the background are studied and presented.